Psychometric properties of the Indonesian Healthcare Providers HIV Stigma Scale: A structural equation modeling approach - Wilandika, Angga; Handayani, Fatiah; Salami, Salami; Elvira, Nunik Ayu (Journal of health psychology, 2025)
HIV-related stigma among healthcare providers hinders effective care delivery, particularly in culturally diverse settings. This study aimed to validate the Indonesian Healthcare Providers’ HIV Stigma Scale using a predictive structural equation modeling (SEM) approach with Partial Least Squares (PLS). A cross-sectional survey involving 138 healthcare providers in Bandung, Indonesia, was conducted to assess the scale’s psychometric properties. The finalized scale comprised 30 items across three constructs—stereotype, prejudice, and discrimination—demonstrating strong construct reliability, convergent validity, and discriminant validity. Results affirm the scale’s utility for assessing stigma, providing a foundation for targeted interventions to mitigate stigma and promote equitable healthcare practices. By offering a culturally adapted measurement tool, this study contributes to improving HIV care and reducing provider-based stigma in Indonesia.